2016
DOI: 10.1038/ncomms13437
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchical zwitterionic modification of a SERS substrate enables real-time drug monitoring in blood plasma

Abstract: Surface-enhanced Raman spectroscopy (SERS) is an ultrasensitive analytical technique with molecular specificity, making it an ideal candidate for therapeutic drug monitoring (TDM). However, in critical diagnostic media including blood, nonspecific protein adsorption coupled with weak surface affinities and small Raman activities of many analytes hinder the TDM application of SERS. Here we report a hierarchical surface modification strategy, first by coating a gold surface with a self-assembled monolayer (SAM) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
131
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 181 publications
(134 citation statements)
references
References 45 publications
1
131
0
2
Order By: Relevance
“…Excellent fouling resistance has been recently reported for ultra‐low fouling polymer brushes 2. Examples include nonionic poly(2‐hydroxyethyl methacrylate), poly(3‐hydroxypropyl methacrylate), poly( N ‐(2‐hydroxypropyl)methacrylamide) (pHPMAA), zwitterionic poly(carboxybetaine)‐based (pCB) brushes such as poly(carboxybetaine methacrylamide) (pCBMAA) and poly(carboxybetaine acrylamide) (pCBAA), or recently developed random copolymers combining zwitterionic and nonionic moieties such as p(CBMAA‐ co ‐HPMAA) 1,2,5,6. These platforms are characterized by diverse physicochemical surface properties including structure, architecture, thickness, rigidity, wettability, surface charge, packing density, or swelling properties; all of these parameters have been shown to have an impact on resulting surface resistance to fouling from complex media and biological activity of immobilized biorecognition elements 5,7.…”
Section: Introductionmentioning
confidence: 99%
“…Excellent fouling resistance has been recently reported for ultra‐low fouling polymer brushes 2. Examples include nonionic poly(2‐hydroxyethyl methacrylate), poly(3‐hydroxypropyl methacrylate), poly( N ‐(2‐hydroxypropyl)methacrylamide) (pHPMAA), zwitterionic poly(carboxybetaine)‐based (pCB) brushes such as poly(carboxybetaine methacrylamide) (pCBMAA) and poly(carboxybetaine acrylamide) (pCBAA), or recently developed random copolymers combining zwitterionic and nonionic moieties such as p(CBMAA‐ co ‐HPMAA) 1,2,5,6. These platforms are characterized by diverse physicochemical surface properties including structure, architecture, thickness, rigidity, wettability, surface charge, packing density, or swelling properties; all of these parameters have been shown to have an impact on resulting surface resistance to fouling from complex media and biological activity of immobilized biorecognition elements 5,7.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the sensing behavior of synthetic receptor assemblies on the devices' surfaces can be sensitively detected. Hung et al reported real-time monitoring of drugs in blood plasma by using SERS-based devices functionalized with SAMs for chemical sensing [44]. In addition, the surface of the prepared SERS device was also coated by a zwitterionic poly(carboxybetaine) layer (PCBAA) to reduce the non-specific adsorption of plasma proteins ( Figure 10).…”
Section: Transduction Of Sensing Information Based On "Invisible" Chamentioning
confidence: 99%
“…Schematic representation of the SERS-based protein sensor functionalized with the mixed SAM. Reproduced and adapted with permission from reference[44]. Copyright 2016 Springer Nature Limited.…”
mentioning
confidence: 99%
“…polyethyleneglycol or proteins. A recent report showed the hierarchical modification of the plasmonic transducer by a combination of a short probing ligand and a longer anti-fouling ligand, to detect doxorubicin spiked in whole blood at the micromolar range [122]. It should be noted that each application requires a different design and additional examples can be found in recent reviews focusing on the advances of SERS for in vivo diagnosis [107] and food safety [100].…”
Section: The Relevance Of Surface Chemistrymentioning
confidence: 99%